A proposal to improve our understanding of entrepreneurship using the Panel Study of Income Dynamics (2008)
This paper aims to evidence how relatively marginal changes in the Panel Study of Income Dynamics survey, particularly on the measurement of returns to entrepreneurship -both financial and human capital- can yield sizeable benefits for research and policy on entrepreneurship. Accurate measurement of returns to all the resources invested in entrepreneurial endeavors is not only essential to understand the motivations and barriers to start a business, but can ultimately provide the basis to improve the effectiveness of programs and policies to foster entrepreneurial activity in the economy. In fact, recent studies question the importance of pecuniary benefits in the decision to become an entrepreneur. However, these are based on measures of total earnings and sample aggregate returns. Thus, adequate individual data on business income and its components has an enormous value for both research and policy design altogether.